Boron nitride catalyst for partial oxidation of hydrocarbons - Garro Mena, Leonardo David (Kansas State University, 2021)
The catalytic activity of hexagonal boron nitride (hBN) is not yet well understood but it seems to be related to hBN hydroxylated sites. A good understanding of those sites and how they are produced is a key step to reveal the true nature of hBN catalytic activity. Here, we report a set of thermal treatments to produce a diversity of hydroxylated sites, as well as a method to remove the boric acid produced by hBN decomposition. We found that some of the boric acid dehydrates on the surface of hBN to produce a borated hBN (hBNO) characterized by an FTIR peak at 1090 cm⁻¹ and an XRD shift due to the variation in the planar distance. When characterizing the thermally treated hBN, the storage of the sample changed the borate’s hydration degree and modified both the XRD pattern and the FTIR spectrum. When stored in a humid environment, boric acid peaks are visible; but when stored in a dry place they are absent. The methods established here are a solid basis for the manufacture, purification and characterization of hBN by thermal treatments, showing how the process can be designed to generate various functional groups on its surface. The thermally treated hBN was also evaluated as a support for Pt during partial oxidation of methane (POM) for the production of syngas. POM is a promising alternative to steam reforming of methane (SRM). POM is an exothermic reaction that requires lower temperatures and less energy than the endothermic SRM. The weaker interaction between Pt and hBN leads to a higher reducibility of Pt, which makes it more active than, for example, Pt/Al₂O₃. In this work we synthesized several Pt catalysts on thermally treated hBN and tested its activity for POM. We discovered that Pt/hBN is more active than Pt/Al₂O₃. The most active catalysts are those where boric acid is present on the surface of hBN before the Pt impregnation. The catalysts prepared this way feature Pt particles on a borated hBN, which makes the Pt-support interaction even weaker, increasing its catalytic activity. Finally, the oxidative dehydrogenation (ODH) of ethane was evaluated on thermally treated hBN. The catalytic activity of hBN using the ODH reaction was evaluated on hBN heated with an O₂/C₂H₆/N₂ stream (activated hBN) vs a 100% N₂ stream (non-activated hBN: hBN*). hBN* catalyzed the catalytic dehydrogenation (CDH) of ethane when the temperature was higher than 160 °C. At 160 °C or below, hBN* was activated and the ODH reaction took place. The catalytic activity of hBN for the ODH reaction increased significantly when the thermal treatment was followed by a sonication step and a separation by centrifugation (labeled as hBNO). This sample showed a borated layer characterized by an FTIR vibration at ≈1190 cm⁻¹. We concluded that there are several active sites on hBN catalyzing the ODH reaction, all of them involve oxygen and requires activation or preparation of the catalyst. Future work is needed to explore the nature of these active sites for the design of hBN based catalysts.
Keywords: Hexagonal boron nitride; Oxidative dehydrogenation; Partial oxidation; Syngas; Catalysis